Pemanfaatan IOT (Internet of Things) pada Pelayanan Bobocabin Puncak Bogor Terhadap Kepuasan Pelanggan - Sofiani; Tatiana Putri Yulia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Internet of Things as a concept that connects physical devices to the internet, has provided new possibilities in tourism destination management, enhanced tourist experiences, and environmental monitoring. Start-up Bobobox provides a healing experience amidst the expanse of tea gardens in Puncak Bogor with a series of sophisticated internet of things technologies through Bobocabin, Bobocabin presents an easy check-in process. One of the accommodation companies that has implemented the IOT concept is bobocabin but we can see together that tourism prioritizes hospitality in providing services provided by staff to guests who come. With this shift, this study aims to explore the relationship between IOT and the sustainability and development of the tourism industry. The method used is descriptive quantitative by distributing questionnaires to guests who have stayed before. The ability of the internet of things to integrate several technologies such as the internet, wireless, ZigBee, Bluetooth, infrared, GRPS, 3G and 4G, has been proven to be efficient in increasing comfort for its users to carry out various activities inside or outside the hotel room, which ultimately forms a positive experience for guests during their stay.